The unequal consequences of job loss across countries - Antoine Bertheau; Edoardo Acabbi; Cristina Barceló; Andreas Gulyas; Stefano Lombardi; Raffaele Saggio (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
We document the consequences of losing a job across countries using a harmonized research design applied to seven matched employer-employee datasets. Workers in Denmark and Sweden experience the lowest earnings declines following job displacement, while workers in Italy, Spain, and Portugal experience losses three times as high. French and Austrian workers face earnings losses somewhere in between. Key to these differences is that Southern European workers are less likely to find employment following displacement. Loss of employerspecific wage premiums explains a substantial portion of wage losses in all countries.
Keywords: J30; J63; J64; 330; Job loss Effects; Wage dynamics; Labor turnover; Mass Layoffs